CircXYLT1 suppresses oxidative stress and promotes vascular remodeling in aging mice carotid artery injury model of atherosclerosis via PTBP1 - Gang Li; Donghui Li; Yajing Li; Bingqi Liu (Experimental Gerontology)
Atherosclerosis and aortic aneurysms are prevalent cardiovascular diseases in the elderly, characterized by chronic inflammation and oxidative stress. This study explores the role of CircXYLT1 in regulating oxidative stress and vascular remodeling in age-related vascular diseases. RNA sequencing revealed a significant upregulation of CircXYLT1 in the vascular tissues of aged mice, highlighting its potential role in age-related vascular diseases. Using a carotid artery wire injury model, we performed adeno-associated virus (AAV)-mediated knockdown and overexpression of CircXYLT1. Key oxidative stress markers, including reactive oxygen species (ROS) and malondialdehyde (MDA), were measured. Knockdown of CircXYLT1 increased oxidative stress and reduced antioxidant protein expression (SOD, GPX), while overexpression led to decreased oxidative damage and enhanced vascular smooth muscle cell (VSMC) proliferation. Mechanistically, CircXYLT1 interacted with PTBP1, reducing its nuclear localization and modulating downstream chemokine signaling pathways. These findings suggest that CircXYLT1 plays a critical role in vascular remodeling and oxidative stress regulation, offering potential as a therapeutic target for managing cardiovascular diseases in aging populations.